ACVR1 is essential for periodontium development and promotes alveolar bone formation. (November 2018) - Zhang, Xue; Liu, Qilin; Zhao, Huan; Hu, Yue; Liu, Cangwei; Yan, Guangxing; Li, Daowei; Mishina, Yuji; Shi, Ce; Sun, Hongchen
Highlights: ACVR1 is essential for periodontium formation. ACVR1 promotes osteoblast differentiation and inhibits osteoclast differentiation to promote alveolar bone formation. ACVR1 promotes the differentiation of fibroblasts and the formation of periodontal ligaments. ACVR1 has little function on cellular cementum at PN21. This is the first study to explain the importance of ACVR1 in regulating periodontium formation. Abstract: Objective: To explore the role of a BMP type I receptor (ACVR1) in regulating periodontium development, Acvr1 was conditionally disrupted in Osterix -expressing cells. Methods: Mandibles from both control ( Acvr1 fx /+; Osterix -Cre (+)/(-)) and cKO ( Acvr1 fx /-; Osterix -Cre (+)/(-)) mice at postnatal day 21 (PN21) were scanned by micro-CT, followed by decalcification and histological observations. Distributions and levels of differentiation markers of fibroblasts, osteoblasts and cementocytes in the periodontium were detected by immunohistochemical (IHC) staining. Results: Micro-CT results showed that bone mass and bone mineral density of the alveolar bones in the cKO mice were lower than those in the controls. Histomorphometry within the alveolar bones revealed that the lower bone mass observed in the cKO mice was caused by increased numbers and resorption activities of osteoclasts. The markers for osteoblast differentiation, Col I and DMP1, were reduced and the signals of the RANKL/OPG ratio were increased in the alveolar bones of the cKO mice compared to those of the control mice. The periodontal ligament in the cKO mice exhibited disorganized collagen fibers with weaker signals of Col I and periostin. However, there was no difference in terms of the cellular cementum between the two groups. Conclusion: ACVR1 is essential for normal periodontium development. ACVR1 in the osteoblasts negatively regulates osteoclast differentiation in association with the RANKL/OPG axis and thus promotes alveolar bone formation.